(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Introduction: An analysis of recent trends, gleaned from diverse healthcare institutions globally, indicates a rising demand for support staff to undertake expanded roles, such as medication reconciliation and patient education. This systematic review aimed of this review is to provide insights that will inform evidence-based strategies for optimizing support staff contributions to medication safety in healthcare settings. Methods: In this systematic review, a meticulous literature search utilizing MeSH terms and keywords related to medication safety and support staff contributions, conducted until August 2022, covered major databases including PubMed/MEDLINE, Cochrane Library, Embase, and CINAHL. The inclusion criteria were limited to clinical trials investigating support staff roles in medication safety within healthcare settings, with rigorous screening processes involving title and abstract reviews followed by full-text assessments. Data extraction involved key elements such as study design, sample size, interventions, and outcomes, contributing to a qualitative synthesis of included clinical trials. Methodological quality was evaluated using the Cochrane Risk of Bias Tool, ensuring a comprehensive and ethically sound past-tense methodology, enhancing the reliability and validity of the review’s findings in understanding support staff contributions to medication safety in healthcare settings, with a particular emphasis on clinical trials. Results: In this systematic review encompassing seven clinical trials with diverse sample sizes (155 to 1,822 participants), aggregated data indicated a notable 25% average reduction in reported medication errors post-intervention, emphasizing the substantial enhancement in medication safety practices linked to support staff contributions [9-16]. Patient demographics across the trials exhibited diversity, with participants spanning various age groups, genders, and ethnic backgrounds. Notably, targeted interventions, including training programs and technological solutions like CPOE systems, demonstrated statistically significant improvements, such as a 21% increase in successful interprofessional communication and a 15% reduction in medication errors attributed to data entry issues [18-20]. These findings underscore the multifaceted impact of support staff in optimizing medication safety across varied patient populations and healthcare contexts. Conclusions: Our systematic review strengthens the evidence base affirming the pivotal contribution of support staff to medication safety in healthcare, as evidenced by reductions in medication errors and adverse drug events, improved patient satisfaction, and the positive impact of technological interventions, offering crucial insights for advancing medication safety practices.